Interpersonal Communication Builds Effective Relationships In Social Context - Sri Rahayu; Muhammad Fadly Darwis; Anisa Salsal Bilah; Khikmawanto Khikmawanto (Penerbit Jurnal Indonesia, 2023)
Interpersonal Communication. The term interpersonal refers to the interaction between two ormore people in an organization. Interpersonal communication in the organization is positively and significantly influenced by self-efficacy, leadership behavior and team cohesion in the organization. This means that the higher the self-efficacy, leadership behavior and team cohesiveness, the higher the interpersonal communication activities in the organization. Belief in success ultimately forms a person's courage to communicate,including interpersonal communication. Communication has many benefits. Communication canpreventmis understandingsigns, symbols. Communication iscarriedout bothtraditionaland modern with thetool sranging from thesimples ttothemostmis understanding.